2013
DOI: 10.1073/pnas.1300954110
|View full text |Cite
|
Sign up to set email alerts
|

Female mediation of competitive fertilization success in Drosophila melanogaster

Abstract: How females store and use sperm after remating can generate postcopulatory sexual selection on male ejaculate traits. Variation in ejaculate performance traits generally is thought to be intrinsic to males but is likely to interact with the environment in which sperm compete (e.g., the female reproductive tract). Our understanding of female contributions to competitive fertilization success is limited, however, in part because of the challenges involved in observing events within the reproductive tract of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
186
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(197 citation statements)
references
References 80 publications
10
186
0
1
Order By: Relevance
“…Whether or not the sperm competitive superiority of the B2 haplogroup is intrinsic or dependent on female haplogroup remains to be determined, since only A-haplogroup females were used in this experiment. Given the evidence of male and female genotype effects on sperm competition in other species [44,45], it is possible that sperm competitive ability in C. scorpioides may be influenced by female mitochondrial haplogroup. While haplogroup-dependent cryptic female choice favouring B2 sperm could theoretically account for the B2 male advantage in fertilization, this hypothesis is not consistent with the results of our assessment of possible haplotype effects on female reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not the sperm competitive superiority of the B2 haplogroup is intrinsic or dependent on female haplogroup remains to be determined, since only A-haplogroup females were used in this experiment. Given the evidence of male and female genotype effects on sperm competition in other species [44,45], it is possible that sperm competitive ability in C. scorpioides may be influenced by female mitochondrial haplogroup. While haplogroup-dependent cryptic female choice favouring B2 sperm could theoretically account for the B2 male advantage in fertilization, this hypothesis is not consistent with the results of our assessment of possible haplotype effects on female reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified female innervation that modulates MP ejection and showed that this behavior has an impact on fertility (Lee et al 2015). MP ejection may be important in postcopulatory sexual selection because the timing of ejection influences the fertilization success of competing males (Lüpold et al 2013).Some functions of the D. melanogaster AMP are known. Females that do not receive the SFP Acp36DE during mating do not form an AMP (Bertram et al 1996) and fail to store sperm at optimal levels (Neubaum and Wolfner 1999;Bloch Qazi and Wolfner 2003).…”
mentioning
confidence: 99%
“…A recent study identified female innervation that modulates MP ejection and showed that this behavior has an impact on fertility (Lee et al 2015). MP ejection may be important in postcopulatory sexual selection because the timing of ejection influences the fertilization success of competing males (Lüpold et al 2013).…”
mentioning
confidence: 99%
“…In mammals, paternally derived genes are thought to increase maternal investment (reviewed in Wilkins & Haig, 2003). However this focus on the male portion of reproduction manipulating the female can potentially obscure the female's role, as it is both sexes that contribute to the social environment (Lupold et al, 2013), where traits of one sex are both genetic contributions to the environment for the other sex and an evolving trait (Moore et al, 1997;Wolf et al, 1998;Wigby & Chapman, 2004;Pischedda et al, 2011).…”
Section: (3) Reproductive Outputmentioning
confidence: 99%
“…Therefore, females provide an interactive rather than a static environment (Lupold et al, 2013). This could explain why heritability estimates of female fertility range from high (Long et al, 2009) to low (Fernandez et al, 2003).…”
Section: (3) Reproductive Outputmentioning
confidence: 99%